The Relationship Between Intrinsic Religiosity and Resilience Among Tunisian Female University Students - Salma Derouiche-El Kamel; Yassamine Hentati-Ghorbel (European Scientific Journal, ESJ, 2025)
This study examines the relationship between intrinsic religiosity and resilience among Tunisian female university students. To achieve this objective, a sample of 244 participants was selected using a self-report method. Participants completed measures assessing intrinsic religiosity and resilience, and the data were analyzed using correlation and linear regression analyses. The results showed a statistically significant, albeit modest, positive correlation between intrinsic religiosity and resilience (p < .001). Furthermore, linear regression analysis showed that intrinsic religiosity accounted for a small but meaningful proportion of the variance in resilience scores (R² = 0.055, p < .001). Based on these findings, it is reasonable to conclude that an increase in intrinsic religiosity contributes to fostering resilience, although this relationship remains modest and is influenced by other unexamined factors. The implications of these findings are discussed in light of the cultural and religious contexts in Tunisia, highlighting the need for further research to explore additional psychological and social factors that may influence this relationship. Finally, this study contributes to the growing body of research on psychological resilience in non-Western, predominantly Muslim contexts, where religiosity may function as a culturally relevant coping mechanism.